2013
DOI: 10.4103/1658-354x.114052
|View full text |Cite
|
Sign up to set email alerts
|

Dose sparing of induction dose of propofol by fentanyl and butorphanol: A comparison based on entropy analysis

Abstract: Background:The induction dose of propofol is reduced with concomitant use of opioids as a result of a possible synergistic action.Aim and Objectives:The present study compared the effect of fentanyl and two doses of butorphanol pre-treatment on the induction dose of propofol, with specific emphasis on entropy.Methods:Three groups of 40 patients each, of the American Society of Anaesthesiologistsphysical status I and II, were randomized to receive fentanyl 2 μg/kg (Group F), butorphanol 20 μg/kg (Group B 20) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Butorphanol can produce a certain degree of sedation and may cause somnolence, respiratory depression or hypoxemia. 22,26,38 But in our study, butorphanol did not prolong extubation time or result in excessive postoperative sedation. This may be related to the use of BIS to adjust the depth of sedation during operation.…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…Butorphanol can produce a certain degree of sedation and may cause somnolence, respiratory depression or hypoxemia. 22,26,38 But in our study, butorphanol did not prolong extubation time or result in excessive postoperative sedation. This may be related to the use of BIS to adjust the depth of sedation during operation.…”
contrasting
confidence: 60%
“…Its effect on KOR activation is dose-dependent and has a ceiling effect. 22 Previous studies have proved that…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Similar findings were reported in studies by Verma RK et al and Kaur J et al, where it was stated that no significant differences were observed between the butorphanol and fentanyl groups in terms of the length of intubation and operation. 5,6 In terms of the hemodynamic response, both the drugs were hemodynamically stable for heart rate, systolic, and diastolic blood pressure, and there was a significant change in the hemodynamic response over time (Table 2). However, it was shown that there was a significant statistical difference in hemodynamic stability between the patients in the butorphanol group and those in the fentanyl group.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, epidural butorphanol was compared to epidural fentanyl for lower abdominal surgery in terms of efficacy and safety. 5,6 Given the present body of knowledge, it is crucial to find a more efficient agent to reduce pain during propofol induction during abdominal procedures and a more effective agent for hemodynamic stability and the requirement for rescue analgesia. There isn't much research on the topic in this part of the country.…”
Section: Introductionmentioning
confidence: 99%